(untitled) (Research, Society and Development, 2025)
Nowadays, the use of literature as a tool for teaching English in schools is becoming increasingly rare due to several obstacles: the advent of information technology, lack of interest in reading, unprepared teachers, inadequate materials, and lack of motivation among students (Zafalon, 2010). In view of the richness that literature can offer to the teaching and learning of English, this article seeks to revive literary texts in the classroom, showing how short stories can be used as an English as a foreign language tool to develop students’ language skills, and presenting the positive points of this pedagogical technique, such as motivation, teaching literary elements, teaching culture and critical thinking. For this, a teaching project is described through two detailed lesson plans, with different activities on vocabulary, grammar, literary elements and text interpretation, using the short story “After Twenty Years”, by O. Henry. The theoretical basis is provided by authors such as Zafalon (2010), Hull (2024), Lazar (1993), Pardede (2011), Erkaya (2005), Kurdi and Nizam (2022), among others. Thus, this article will be very useful to the school community, helping to rekindle students’ interest in reading, since the stories are short, which will help them improve their English proficiency. In addition, teachers will be able to diversify their classes, making them more interesting and beneficial, as well as encouraging the reading of literary works.